Influence of rice variety and grain form on the development and infestation of Sitophilus oryzae (L.): A comparative analysis - Geteneh Mitku Chekol (PLoS ONE, 2025)
Post harvest losses caused by the rice weevil ( Sitophilus oryzae L .) pose a severe threat to food security and farmer income in Ethiopia. While both rice variety and grain processing form (paddy, brown, polished) influence susceptibility, their interaction in locally adapted Ethiopian varieties remains unquantified, limiting the development of effective resistance-based storage strategies. A controlled laboratory study was conducted using a three-factor factorial experiment in a completely randomized design (CRD) with seven replicates per treatment (n = 7), totaling 126 experimental units. Six Ethiopian rice varieties (Nerica-4, Gumara, Selam, Shaga, Wanzaye, and X-Jigna) were tested across three grain forms. Each replicate consisted of 50 g of grain infested with 20 unsexed adult weevils. Key parameters measured were development time, F₁ progeny emergence (as a measure of fecundity), percentage grain damage, weight loss, and the Dobie Susceptibility Index (DI).Grain form was the dominant factor affecting weevil performance. Polished rice significantly accelerated development (mean = 29.86 days) and increased progeny production (mean = 40.38 adults) and grain damage (21.83%) compared with brown rice (29.81 progeny, 6.79–13.86% damage) and paddy rice (23.29 progeny, 8.29–16.00% damage). This represents up to a 42.3% reduction in progeny emergence and a 69.9% reduction in grain damage when storing brown rather than polished rice. A significant variety × grain form interaction (p < 0.05) revealed that polished Gumara and X-Jigna were the most susceptible combinations, while brown and paddy Nerica-4 showed the strongest resistance. The Dobie Index was strongly positively correlated with progeny count (r = 0.859, p < 0.001) and negatively correlated with development time (r = −0.912, p < 0.001), supporting its validity as a resistance metric. Grain width showed a weak but significant negative correlation with weight loss (r = −0.227, p = 0.011). The high susceptibility of polished rice and the strong resistance of Nerica-4 provide a clear strategy for loss reduction. Promoting the storage of paddy or brown rice of resistant varieties like Nerica-4 can significantly mitigate postharvest losses, reduce pesticide reliance, and enhance food security in Ethiopia.